Ultrasonic attenuation of an agar, silicon dioxide, and evaporated milk gel phantom - Drakos, Theocharis; Antoniou, Anastasia; Evripidou, Nikolas; Alecou, Tereza; Giannakou, Marinos; Menikou, Georgios; Constantinides, Georgios; Damianou, Christakis A. (My University, 2021)
Background: It has been demonstrated that agar-based gel phantoms can emulate the acoustic parameters of real tissues and are the most commonly used tissue-mimicking materials for high-intensity focused ultrasound applications. The following study presents ultrasonic attenuation measurements of agar-based phantoms with different concentrations of additives (percent of agar, silicon dioxide and evaporated milk) in an effort of matching the material's acoustic property as close as possible to human tissues. Methods: Nine different agar-based phantoms with various amounts of agar, silicon dioxide, and evaporated milk were prepared. Attenuation measurements of the samples were conducted using the through-transmission immersion techniques. Results: The ultrasonic attenuation coefficient of the agar-based phantoms varied in the range of 0.30-1.49 dB/cm-MHz. The attenuation was found to increase in proportion to the concentration of agar and evaporated milk. Silicon dioxide was found to significantly contribute to the attenuation coefficient up to 4% weight to volume (w/v) concentration. Conclusion: The acoustic attenuation coefficient of agar-based phantoms can be adjusted according to the tissue of interest in the range of animal and human tissues by the proper selection of agar, silicon dioxide, and evaporated milk.
Keywords: Agar; Attenuation; Tissue‑mimicking material; Ultrasound